It Is Time to Dance with Dragons - Niles, Damayanthi M.A. (International review of mission, 2011)
How can we live today between what is unknown (the dragon) and what is known or familiar, between comprehension and mystery? Three concepts that have figured prominently in the IRM are critically examined here – “ecumenical,” “salvation history” and missio Dei. Originally richly open terms pointing to God and God's whole world, through the years they have been domesticated in order to fit with what is known, thereby reducing their fullness and mystery. They need to be creatively and dialogically expanded amid the plurality in which we live today.